Insultos, amenazas y maldiciones en el campo de batalla: las reprimendas entre aliados en la Ilíada - Conti Jimenez, Luz (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2025)
In the Iliad, certain harangues characterized by the accumulation of insults, threats and curses, can be analyzed as macro-speech acts of reprimand. These macro-speech acts show both a similar structure and similar linguistic strategies. The impoliteness of these reprimands is normalized and thus acceptable to both speaker and interlocutor. It is an institutional impoliteness that uses the humiliation of the interlocutor as a mean of reaffirming the values of the army to which he belongs.
Keywords: Iliad; speech acts of rebuke; reprimands; impoliteness; institutional impoliteness